Reception and integration practices for migrants in Costa Rica and República Dominicana - Fouillioux Bambach, Matías (2025)
The objective of this contribution is to identify and analyze the policies, practices of integration and protection of migrants, asylum seekers and refugees in vulnerable situations in Central America and the Caribbean, specifically through two case studies: Costa Rica and Dominican Republic; based on concepts such as sanctuary cities, hospitality, and solidarity, associated with the sanctuary movement that originated in the United States in the 1980s. The results show, on the one hand, a low rate of approval and processing of asylum applications, so that the practices of reception and integration of the population subject to study acquire greater relevance. However, there is a clear difference in the implementation of the concept with respect to the global north, due to the complexity of the migratory categories in the region and because they do not represent an opposition or resistance to local policies because they are intergovernmental agreements.